Riding the Lexical Speedway: A Critical Review on the Time Course of Lexical Selection in Speech Production - Strijkers, Kristof; Costa, Albert (Frontiers in Psychology, 2011)
Speech requires time. How much time often depends on the amount of labor the brain has to perform in order to retrieve the linguistic information related to the ideas we want to express. Although most psycholinguistic research in the field of language production has focused on the net result of time required to utter words in various experimental conditions, over the last years more and more researchers pursued the objective to flesh out the time course of particular stages implicated in language production. Here we critically review these studies, with particular interest for the time course of lexical selection. First, we evaluate the data underlying the estimates of an influential temporal meta-analysis on language production (Indefrey & Levelt, 2004). We conclude that those data alone are not sufficient to provide a reliable time frame of lexical selection. Next, we discuss recent neurophysiological evidence which we argue to offer more explicit insights into the time course of lexical selection. Based on this evidence we suggest that, despite the absence of a clear time frame of how long lexical selection takes, there is sufficient direct evidence to conclude that the brain initiates lexical access within 200 ms after stimulus presentation, hereby confirming Indefrey and Levelt’s estimate. In a final section, we briefly review the proposed mechanisms which could lead to this rapid onset of lexical access, namely automatic spreading activation versus specific concept selection, and discuss novel data which support the notion of spreading activation, but indicate that the speed with which this principle takes effect is driven by a top-down signal in function of the intention to engage in a speech act.